PERAN PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PRODUK BLACKMORES VITAMIN D3 1000 IU : (STUDI PADA MASYARAKAT BANDUNG DAN JAKARTA) - Belva, Felicia Amanda; Kristiawan, Allen (FEB Universitas Sam Ratulangi Manado, 2024)
The aim of this study is to investigate and assess the relationship between price perception and promotional factors on customer purchasing decisions. This study utilises a quantitative research methodology, adopting a purposive sampling procedure and utilising a questionnaire as the major research instrument. The study included individuals who frequently participate in outdoor activities, have direct exposure to pollution, routinely consume vitamin D, and live in the cities of Bandung and Jakarta. After collecting the data, various tests are performed to determine its validity and reliability. Additionally, classical assumptions are assessed and many regression tests are run. The author's research revealed that consumer purchasing decisions for Blackmores Vitamin D3 10000 IU products were highly influenced by their views of pricing and promotions.